Dosimetric feasibility of ablative dose escalated focal monotherapy with MRI-guided high-dose-rate (HDR) brachytherapy for prostate cancer. Issue 1 (January 2017) - Hosni, Ali; Carlone, Marco; Rink, Alexandra; Ménard, Cynthia; Chung, Peter; Berlin, Alejandro
Abstract: Purpose: To determine the dosimetric feasibility of dose-escalated MRI-guided high-dose-rate brachytherapy (HDR-BT) focal monotherapy for prostate cancer (PCa). Methods: In all patients, GTV was defined with mpMRI, and deformably registered onto post-catheter insertion planning MRI. PTV included the GTV plus 9 mm craniocaudal and 5 mm in every other direction. In discovery-cohort, plans were obtained for each PTV independently aiming to deliver ⩾16.5 Gy/fraction (two fraction schedule) while respecting predefined organs-at-risk (OAR) constraints or halted when achieved equivalent single-dose plan (24 Gy). Dosimetric results of original and focal HDR-BT plans were evaluated to develop a planning protocol for the validation-cohort. Results: In discovery-cohort (20-patients, 32-GTVs): PTV D95% ⩾16.5 Gy could not be reached in a single plan (3%) and was accomplished (range 16.5–23.8 Gy) in 15 GTVs (47%). Single-dose schedule was feasible in 16 (50%) plans. In the validation-cohort (10-patients, 10-GTVs, two separate implants each): plans met acceptable and ideal criteria in 100% and 43–100% respectively. Migration to single-dose treatment schedule was feasible in 7 implants (35%), without relaxing OAR's constraints or increasing the dose (D100% and D35%) to mpMRI-normal prostate ( p  > 0.05). Conclusion: Focal ablative dose-escalated radiation is feasible with the proposed protocol. Prospective studies are warranted to determine the clinical outcomes.